Sinnerswandel - Hausberger, Rita Maria; Wendling, Markus (Germany, 2011)
For most people, the world is shaped by visual sensations. But how do those without eyesight perceive the world around them? A short film about sensory perception and disability.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films